Metal contaminants and chloramphenicol in Litopenaeus vannamei and Penaeus silasi at various supply chain stages in Johor Bahru, Malaysia and their health risk assessment - Anuar, Nurazira; Mahat, Naji Arafat; Muhamad, Ida Idayu; Abdul Keyon, Aemi Syazwani; Mohamed Huri, Mohamad Afiq; Yunus, Nor Alafiza; Abang Zaidel, Dayang Norulfairuz; Abdul-Mutalib, Noor Azira; Radu, Son; Azman, Aida Rasyidah (Elsevier, 2023)
Objectives: This present research evaluated the concentrations of metal contaminants (As, Pb, Cd and total Hg) and chloramphenicol as prescribed by the Malaysian Food Act (1983) and Regulations (2021) in Penaeus silasi and Litopenaeus vannamei shrimps sampled from the different supply chain stages (landing sites, major markets and grocers) in Johor Bahru, Johor, Malaysia at six sampling intervals. Methods: Graphite furnace atomic absorption spectrometer and flow injection mercury/hyride system were used to determine the concentration of As, Pb and Cd as well as total Hg, respectively. Enzyme linked immunosorbent assay was used to determine the concentration of chloramphenicol. Results: The median As and Cd concentrations during the six sampling intervals ranged between below detection limit-167.5 mg/kg and 0.46 mg/kg, respectively. The total Hg concentrations ranged between 0.02 and 1.13 mg/kg. Although Pb and chloramphenicol were not detected, As and total Hg concentrations varied significantly across sampling intervals (P < 0.05), exceeded the maximum permitted proportions prescribed by the Malaysian law. Identified as P. silasi, shrimps from landing sites Mersing and Pontian had significantly higher As and total Hg concentrations than those of L. vannamei from major markets and their surrounding grocers (P < 0.05). Alarmingly, Hazard Index for P. silasi from landing sites Mersing and Pontian as well as L. vannamei from major markets and grocers exceeded 1.00.